Marketing Mix Strategy (4P) of MSME in The Pandemic Time of Covid-19 - Asriadi Arifin; Murtiadi Awaluddin; Amiruddin K; Irwandi; Andi Nur Annisa M (ILIN Institute, 2023)
This research aims to examine the marketing mix strategies implemented by MSMEs during the Covid-19 pandemic. The research method uses descriptive qualitative with a phenomenological approach to obtain an overview of the marketing mix strategy used by MSMEs in Makassar City with the concept of ghost kitchen during the Covid-19 pandemic. Primary data was obtained directly from informants by conducting interviews with the owner of Kaku Food. In this study, secondary data was obtained from reference books, journals, articles, research, magazines, newspapers and websites related to this research. Data collection techniques used include observation, interviews and documentation. The conclusion is Marketing Strategy of MSMEs during the Covid-19 Pandemic is carried out in accordance with the concept of the marketing mix. The marketing scheme is to offer products according to consumer needs at prices that are adjusted between capabilities and consumer economic conditions, and promotions are prioritized on online promotions. That way, MSMEs can maintain their stability and sustainability even though they are experiencing the Covid-19 pandemic.